Employee perseverance in a "no phone use while driving" organizational road-safety intervention. (September 2020) - Rispler, Clara; Luria, Gil
Highlights: An organizational intervention reduced smartphone use while driving. Men persevered in the intervention to a greater degree than women. Organizational safety climate perceptions predicted perseverance in an organizational health intervention. Abstract: Introduction: This interdisciplinary study explores factors that contribute to the perseverance of participants in an organizational "no phone use while driving" road-safety intervention. Method: The study sample comprised 200 employees (mean age 43 years; 104 females [52 %], 96 males [48 %]) from 8 organizations in Israel. Subjects completed a 4-month organizational intervention using a smartphone application that monitored smartphone use, operationalized as taps per minute, where each tap represents a single instance of contact with the screen (e.g., touching, tapping or swiping). The app also silenced notifications during the intervention stage. Changes over time in tapping-while-driving behavior were examined through self-report questionnaires and objectively through the application's monitoring function. Validated measures were used to examine factors associated with perseverance in the program. Results: Organizational safety climate and gender (male) were positively related to perseverance in the intervention. Contrary to our hypothesis, safety motivation was not found to influence perseverance. Conclusions: The present intervention is most effective for employees with high safety climate perceptions and for male employees. Practical applications: The organizational intervention presented in the current study was shown to be effective in reducing smartphone use (touching, tapping or swiping) while driving. Our findings show that people will download and use an app that actively reduces their incentive to use their phones at the wheel by silencing incoming notifications. The findings support calls to harness the positive potential of information and communications technologies for organizational interventions.